The effect of organic fertilizer and mount Merapi volcanic ash to land rehabilitation - Adrinoviarini, Adrinoviarini (Inornatus: Biology Education Journal, 2022)
This study aims to determine the effect of adding organic fertilizer to the ex-eruption of Mount Merapi by using an indicator plant of peanut (Arachis hypogaea L.) Gajah variety in order to land rehabilitation. The treatment used was the addition of volcanic ash and organic fertilizer. The organic fertilizer used comes from chicken manure. The selection of chicken manure as organic fertilizer uses the principle of sustainability, where in the research area there are many chicken farmers so that the presence of chicken manure is easy and cheap to obtain. The design of this study was based on 1 block completely randomized 2 factorial design which was repeated 3 times. With the addition of volcanic ash and chicken manure, 10 tons/ha, 20 tons/ha and 30 tons/ha, respectively. Plant parameters observed were: (1) plant height, (2) fresh weight and dry weight of roots, (3) Shoots' fresh and dry weight, (4) fresh weight and dry weight of pods, (5) Seeds' fresh weight and dry weight, (6) number of seeds and pods/plant, and (7) N uptake and root nodule number. The findings indicated that chicken manure increased plant height from 1 to 5 weeks after planting. The application of 30 tons/ha of chicken manure has raised the height of plants. The addition of chicken manure tends to enhance the peanut seeds' dry weight.